Porous carbon composite material and preparation method and application thereof
By using porous carbon composite materials in the negative electrode of the secondary battery, the low Coulomb efficiency and lithium dendrites growth problems of lithium metal in the negative electrode are solved, and a secondary battery with high energy density, cycle stability and safety is achieved.
Patent Information
- Application Number
- CN202411819977.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is difficult to apply lithium metal to the negative electrode of secondary batteries, due to its low Coulomb efficiency and the growth of lithium dendrites, resulting in limited battery performance and safety problems.
Porous carbon composite materials are used as the negative electrode material, wherein the core includes porous carbon and lithium metal attached to the porous carbon pore walls. By defining the mass percentage of porous carbon, lithium metal and carbon cladding, and controlling the specific surface area, pore volume and lithium metal particle distribution, a specific relationship is satisfied to improve the surface uniformity and stability of the material.
It effectively improves the reversible capacity of the negative electrode material, reduces the local current density, suppresses the formation of lithium crystal branches and the volume expansion of the electrode sheet, avoids direct contact between lithium metal and electrolyte, and improves the energy density, cycle stability and safety of the secondary battery.
Smart Images

Figure BDA0005182866510000131 
Figure BDA0005182866510000141
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a porous carbon composite material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used due to their high energy density, high charging efficiency, superior cycle performance, and high output power. With the continuous advancement of science and technology, higher requirements are placed on the service life and performance of lithium-ion batteries. Lithium is a potentially useful anode material due to its high specific capacity, low redox potential, and ability to supply lithium for the entire battery. However, the practical application of lithium metal anodes is still limited by their low Coulombic efficiency and the growth of lithium dendrites during lithium dissolution / deposition. This tendency of lithium stripping and plating reduces battery performance, resulting in limited cycle life and serious safety issues, which hinders the practical application of batteries using lithium metal in the anode. Summary of the invention
[0003] The purpose of the present application is to solve the technical problem that lithium metal cannot be applied to the negative electrode of a secondary battery in the prior art, and to provide a porous carbon composite material that can be applied to the negative electrode.
[0004] To achieve the above-mentioned object, in a first aspect of the present application, a porous carbon composite material is provided, wherein the porous carbon composite material comprises a core and a carbon coating layer, wherein the core comprises porous carbon and lithium metal attached to the pore walls of the porous carbon;
[0005] Based on the total mass of the porous carbon composite material, the mass percentage of the porous carbon is 80-88%, the mass percentage of the lithium metal is 8-16%, and the mass percentage of the carbon coating layer is 3-5%;
[0006] The specific surface area of the porous carbon composite material is 500-920 m 2 / g, pore volume V is 0.4-0.9cc / g;
[0007] The average number n of lithium metal particles in the porous carbon composite material with an area of 100nm×100nm is 20-30;
[0008] The porous carbon composite material satisfies: 25≤A≤62.5,
[0009] Where A = (n*d2) / 2;
[0010] d2μm is the thickness of the carbon coating layer.
[0011] As an embodiment of the present application, the porous carbon composite material satisfies: 15.6≤D≤22.5,
[0012] Where, D = (d1 + d2) * 0.3;
[0013] d1μm is the radius of the inner core of the porous carbon composite material.
[0014] As an embodiment of the present application, the radius d1 of the inner core of the porous carbon composite material is 50-70 μm, and the thickness of the carbon coating layer is 2-5 μm.
[0015] As an embodiment of the present application, the porous carbon is doped porous carbon, and the doping atoms of the doped porous carbon include at least one of nitrogen, boron, and oxygen.
[0016] As an embodiment of the present application, based on the total mass of the porous carbon, the mass percentage of the doping atoms is 2-5%.
[0017] As an embodiment of the present application, the carbon coating layer is a doped carbon coating layer, and the doping atoms of the doped carbon coating layer include at least one of nitrogen, boron and oxygen.
[0018] As an embodiment of the present application, the mass percentage of the doping atoms is 2-5% based on the total mass of the carbon coating layer.
[0019] In a second aspect of the present application, the present application provides a method for preparing the porous carbon composite material, the preparation method comprising the following steps:
[0020] (1) mixing the lithium salt solution and the porous carbon with stirring and ultrasonication to obtain a suspension;
[0021] (2) adding aluminum chloride to the suspension for electrolysis, centrifuging after electrolysis, collecting the solid and calcining to obtain an intermediate;
[0022] (3) The intermediate is carbon-coated and then vacuum-freezed to obtain a porous carbon composite material.
[0023] As an embodiment of the present application, in the step (1), the frequency of ultrasound is 60-100 KHz, and the time of ultrasound is 20-40 min.
[0024] As an embodiment of the present application, in the step (2), the calcination temperature is 1000-1200° C., and the calcination time is 1.5-2.5 h.
[0025] As an implementation scheme of the present application, in the step (3), the vacuum freeze-drying temperature is -25 to -30°C, and the vacuum freeze-drying time is 20 to 28 hours.
[0026] As an embodiment of the present application, the lithium salt includes at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium boron trifluoride, lithium hexafluorophosphate, lithium tetrahydrofuran ester, 3,4-dihydroxybenzonitrile dilithium, n-butyl lithium, methyl lithium, and phenyl lithium.
[0027] In the third aspect of the present application, the present application provides the use of the porous carbon composite material in preparing electrode materials.
[0028] In the fourth aspect of the present application, the present application provides a negative electrode plate, which includes a negative electrode collector and a negative electrode active material layer arranged on at least one side of the negative electrode collector, and the negative electrode active material layer includes the porous carbon composite material, conductive agent, thickener and binder described in the present application; based on the total mass of the negative electrode active material layer, the mass percentage of the porous carbon composite material is 95-98%.
[0029] In a fifth aspect of the present application, the present application provides a secondary battery, wherein the secondary battery comprises the negative electrode plate described in the present application.
[0030] Compared with the prior art, the beneficial effects of this application are:
[0031] A porous carbon composite material provided in the present application includes a core and a carbon coating layer, wherein the core includes porous carbon and lithium metal attached to the pore walls of the porous carbon, and the mass percentages of the porous carbon, lithium metal and carbon coating layer are limited to a certain range, and the specific surface area, pore volume and average number of lithium metal particles per unit area of the porous carbon composite material are within a certain range, and the porous carbon composite material satisfies a specific relationship 25≤(n*d2) / 2≤62.5, and the obtained porous carbon composite material has excellent surface uniformity. When used as a negative electrode material in the preparation of secondary batteries, it can effectively improve the reversible capacity of the negative electrode material, reduce the local current density of the negative electrode plate, and inhibit the formation of lithium dendrites and the volume expansion of the negative electrode plate during the cycle. In addition, the porous carbon composite material provided in the present application can also effectively avoid direct contact between lithium metal and electrolyte, and avoid the influence of interfacial side reactions on the coulombic efficiency of the secondary battery; thereby achieving excellent energy density, cycle stability and safety of the secondary battery. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0033] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0034] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0035] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0036] In one embodiment of the present application, the present application proposes a porous carbon composite material, the porous carbon composite material comprising a core and a carbon coating layer, the core comprising porous carbon and lithium metal attached to the porous carbon pore wall;
[0037] Based on the total mass of the porous carbon composite material, the mass percentage of the porous carbon is 80-88%, the mass percentage of the lithium metal is 8-16%, and the mass percentage of the carbon coating layer is 3-5%;
[0038] The specific surface area of the porous carbon composite material is 500-920 m 2 / g, pore volume V is 0.4-0.9cc / g;
[0039] The average number n of lithium metal particles in the porous carbon composite material with an area of 100nm×100nm is 20-30;
[0040] The porous carbon composite material satisfies: 25≤A≤62.5,
[0041] Where A = (n*d2) / 2;
[0042] d2μm is the thickness of the carbon coating layer.
[0043] The present application has found that by limiting the mass percentages of porous carbon, lithium metal and carbon coating within a certain range, and the specific surface area, pore volume and average number of lithium metal particles per unit area of the porous carbon composite material within a certain range, and the porous carbon composite material satisfies the specific relationship 25≤(n*d2) / 2≤62.5, the obtained porous carbon composite material has excellent surface uniformity. When used as a negative electrode material in the preparation of secondary batteries, it can effectively improve the reversible capacity of the negative electrode material, reduce the local current density of the negative electrode plate, and inhibit the formation of lithium dendrites and the volume expansion of the negative electrode plate during the cycle. In addition, the porous carbon composite material provided in the present application can also effectively avoid direct contact between lithium metal and electrolyte, and avoid the influence of interfacial side reactions on the coulombic efficiency of the secondary battery; thereby achieving excellent energy density, cycle stability and safety of the secondary battery.
[0044] Specifically, when the mass percentage of the porous carbon in the porous carbon composite material of the present application is between 80-88%, it has excellent chemical stability and mechanical properties as the main part of the porous carbon composite material, provides a uniform and stable carbon skeleton structure, and has a large specific surface area, which provides sufficient active sites for the embedding of lithium metal. The lithium metal content in the appropriate mass percentage range can ensure that most of the lithium metal is attached to the pore wall of the porous carbon rather than exposed on the surface of the porous carbon, thereby avoiding lithium as a reaction nucleus on the porous carbon surface to cause more lithium dendrite growth, thereby ensuring that the secondary battery obtained when it is used as a negative electrode material in the preparation of the secondary battery has high coulombic efficiency and excellent cycle performance. The introduction of the carbon coating layer in the appropriate mass percentage range can effectively avoid the direct contact between the subsequent lithium metal and the electrolyte, and can also avoid the influence on the deintercalation and electron transfer of lithium ions, thereby improving the energy density, safety performance and cycle performance of the secondary battery. The specific surface area and pore volume in the appropriate range can provide sufficient reactive active sites to ensure the deintercalation and electron transfer of lithium ions in the material, thereby helping to achieve the excellent energy density and cycle performance of the secondary battery. The average number of lithium metal particles per unit area in the porous carbon composite material is within a certain range, which can ensure the uniformity of lithium metal distribution, thereby effectively improving the comprehensive performance of the secondary battery prepared subsequently. Furthermore, when the porous carbon composite material satisfies the specific relationship 25≤(n*d2) / 2≤62.5, it can effectively balance the lithium metal attached to the porous carbon pore wall and the lithium metal exposed on the porous carbon surface, and set the appropriate thickness of the carbon coating layer according to the amount of lithium metal exposed, which can avoid the reaction of lithium metal with the electrolyte without affecting the deintercalation and transmission of ions and electrons in the porous carbon composite material, thereby achieving excellent comprehensive performance of the secondary battery.
[0045] It should be noted that the mass percentages of the porous carbon, lithium metal and carbon coating layer, based on the total mass of the porous carbon composite material, are tested by infrared spectroscopy and EDS testing.
[0046] It should be noted that the specific surface area of the porous carbon composite material is tested by the BET method, and the pore volume is tested by the N2 adsorption method.
[0047] It should be noted that the test method for the average number of lithium metal particles in the 100nm×100nm area of the porous carbon composite material is EDS and laser particle size analysis.
[0048] Exemplarily, based on the total mass of the porous carbon composite material, the mass percentage of the porous carbon can be any point value between 80-88% or any two point range values, such as 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, etc.; the mass percentage of the lithium metal can be any point value between 8-16% or any two point range values, such as 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, etc.; the mass percentage of the carbon coating layer can be any point value between 3-5% or any two point range values, such as 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, etc.
[0049] For example, the porous carbon composite material may have a BET specific surface area of 500-920 m 2 Any point value or any range value between two points, for example, 500m 2 / g, 550m 2 / g、600m 2 / g, 650m 2 / g、700m 2 / g, 750m 2 / g、800m 2 / g, 850m 2 / g、900m 2 / g, 920m 2 / g, etc.; the pore volume V can be any point value between 0.4-0.9cc / g or any two points in the range, for example, 0.4cc / g, 0.45cc / g, 0.5cc / g, 0.55cc / g, 0.6cc / g, 0.65cc / g, 0.7cc / g, 0.75cc / g, 0.8cc / g, 0.85cc / g, 0.9cc / g, etc.
[0050] Exemplarily, in the 100nm×100nm area of the porous carbon composite material, the average number n of lithium metal particles can be any point value between 5-20 or any two point range values, for example, 5, 8, 10, 12, 14, 16, 18, 20, etc.
[0051] Exemplarily, A may be any point value or any two point range value between 20-75, for example, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, etc.
[0052] In one embodiment, based on the total mass of the porous carbon composite material, the mass percentage of the porous carbon is 83-85%, the mass percentage of the lithium metal is 11-13%, and the mass percentage of the carbon coating layer is 4%.
[0053] The present application study found that when the porous carbon composite material is further selected, and the mass percentages of the porous carbon, lithium metal and carbon coating layer are within the above range, when the obtained product is used as a negative electrode material in a secondary battery, the comprehensive performance of the obtained secondary battery is better.
[0054] In one embodiment, the porous carbon composite material has a BET specific surface area of 650-750 m 2 / g, and the pore volume V is 0.7-0.8cc / g.
[0055] The research in this application found that the specific surface area and pore volume of the porous carbon composite material have a certain relationship with its morphology and stability. When the specific surface area and pore volume of the porous carbon composite material are further selected to be within the above-mentioned range, the obtained porous carbon composite material has excellent stability. When used as a negative electrode material in the preparation of secondary batteries, it can prevent the local current density of the secondary battery from being too high and causing the local temperature of the secondary battery to rise too high, thereby improving the safety of the secondary battery; at the same time, it can also ensure the number of effective active sites, thereby helping to improve the coulombic efficiency of the secondary battery.
[0056] In one embodiment, the porous carbon composite material satisfies: 35≤A≤40.
[0057] The present application study found that when a porous carbon composite material is further selected to satisfy 35≤A≤40 and subsequently applied to the preparation of a secondary battery, the overall performance of the resulting secondary battery is better.
[0058] In one embodiment, the porous carbon composite material satisfies: 15.6≤D≤22.5,
[0059] Where, D = (d1 + d2) * 0.3;
[0060] d1μm is the radius of the inner core of the porous carbon composite material.
[0061] Exemplarily, D may be any point value or any two point range value between 15.6-22.5, for example, it may be 15.6, 16, 17, 18, 19, 20, 21, 22, 22.5, etc.
[0062] The research in this application found that an inner core that is too large will cause the volume of the composite material to be too large, affecting the compaction and rebound of the negative electrode material and the adhesion of the electrode sheet, and an overly thick coating will affect the ion transmission efficiency; similarly, an inner core that is too small will affect the deposition of lithium metal, and an overly thin carbon coating will not be able to effectively isolate lithium metal from the electrolyte; only when 15.6≤(d1+d2)*0.3≤22.5 is further selected, and the obtained product is applied to the preparation of secondary batteries, the obtained secondary batteries have excellent comprehensive performance.
[0063] In one embodiment, the radius d1 of the inner core of the porous carbon composite material is 50-70 μm, and the thickness d2 of the carbon coating layer of the porous carbon composite material is 2-5 μm.
[0064] It should be noted that the radius d1 of the inner core of the porous carbon composite material and the thickness d2 of the carbon coating layer are tested by high-power transmission electron microscopy (HRTEM) imaging and calculation and analysis of lattice fringe parameters.
[0065] Exemplarily, the thickness d1 of the inner core of the porous carbon composite material can be any point value or any two point range values between 50-70μm, for example, it can be 50μm, 53μm, 55μm, 58μm, 60μm, 63μm, 65μm, 68μm, 70μm, etc.; the thickness d2 of the carbon coating layer of the porous carbon composite material can be any point value or any two point range values between 2-5μm, for example, it can be 2μm, 2.3μm, 2.5μm, 2.8μm, 3μm, 3.3μm, 3.5μm, 3.8μm, 4μm, 4.3μm, 4.5μm, 4.8μm, 5μm, etc.
[0066] The present application has found that by further selecting the radius of the inner core of the porous carbon composite material and the thickness of the carbon coating layer within the above range, the stability of the porous carbon composite material can be improved. When it is used as a negative electrode material in the preparation of secondary batteries, direct contact between lithium metal and electrolyte can be avoided, and the deintercalation and electron transfer of lithium ions will not be affected, thereby improving the overall performance of the secondary battery.
[0067] In one embodiment, the porous carbon is doped porous carbon, and the doping atoms of the doped porous carbon include at least one of nitrogen, boron, and oxygen. In one embodiment, the carbon coating layer is a doped carbon coating layer, and the doping atoms of the doped carbon coating layer include at least one of nitrogen, boron, and oxygen. It should be noted that the types of doping atoms of the doped porous carbon and the doped carbon coating layer are obtained through SEM and XRD tests.
[0068] The research in this application found that further heteroatom doping in the porous carbon and the carbon coating layer can facilitate the heterogeneous nucleation of lithium metal, and is more conducive to the close bonding of carbon and lithium metal, thereby improving the stability of the porous carbon composite material.
[0069] In one embodiment, based on the total mass of the porous carbon, the mass percentage of the doping atoms is 2-5%.
[0070] In one embodiment, based on the total mass of the carbon coating layer, the mass percentage of the doping atoms is 2-5%.
[0071] It should be noted that the mass percentage of doped atoms in the doped porous carbon and the doped carbon coating layer is tested by EDS and XRD.
[0072] Exemplarily, based on the total mass of the porous carbon, the mass percentage of the doping atoms can be any point value between 2-5% or any two points in the range, such as 2%, 2.3%, 2.5%, 2.8%, 3%, 3.3%, 3.5%, 3.8%, 4%, 4.3%, 4.5%, 4.8%, 5%, etc.
[0073] Exemplarily, based on the total mass of the carbon coating layer, the mass percentage of the doping atoms can be any point value between 2-5% or any two point range values, such as 2%, 2.3%, 2.5%, 2.8%, 3%, 3.3%, 3.5%, 3.8%, 4%, 4.3%, 4.5%, 4.8%, 5%, etc.
[0074] In one embodiment of the present application, the present application provides a method for preparing the porous carbon composite material, the preparation method comprising the following steps:
[0075] (1) mixing the lithium salt solution and the porous carbon with stirring and ultrasonication to obtain a suspension;
[0076] (2) adding aluminum chloride to the suspension for electrolysis, centrifuging after electrolysis, collecting the solid and calcining to obtain an intermediate;
[0077] (3) The intermediate is carbon-coated and then vacuum-freezed to obtain a porous carbon composite material.
[0078] The present application has found that the preparation method provided in the present application can effectively obtain the corresponding porous carbon composite material.
[0079] In one embodiment, in step (1), the frequency of ultrasound is 60-100 KHz, and the time of ultrasound is 20-40 min.
[0080] Exemplarily, the frequency of the ultrasound can be any point value or any two point range value between 60-100KHz, such as 60KHz, 70KHz, 80KHz, 90KHz, 100KHz, etc.; the time of the ultrasound can be any point value or any two point range value between 20-40min, such as 20min, 25min, 30min, 35min, 40min, etc.
[0081] In one embodiment, in the step (2), the calcination temperature is 1000-1200° C., and the calcination time is 1.5-2.5 h.
[0082] Exemplarily, the calcination temperature may be any point value or any two points in the range of 1000-1200°C, such as 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, etc.; the calcination time may be any point value or any two points in the range of 1.5-2.5h, such as 1.5h, 2h, 2.5h, etc.
[0083] In one embodiment, in step (3), the vacuum freeze-drying temperature is -25 to -30°C, and the vacuum freeze-drying time is 20 to 28 hours.
[0084] Exemplarily, the temperature of the vacuum freeze-drying can be any point value or any two points in the range between -25 and -30°C, such as -25°C, -26°C, -27°C, -28°C, -29°C, -30°C, etc.; the time of the vacuum freeze-drying can be any point value or any two points in the range between 20-28h, such as 20h, 22h, 24h, 26h, 28h, etc.
[0085] In one embodiment, the lithium salt includes at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium boron trifluoride, lithium hexafluorophosphate, lithium tetrahydrofuran ester, 3,4-dihydroxybenzonitrile dilithium, n-butyl lithium, methyl lithium, and phenyl lithium.
[0086] In one embodiment, the porous carbon and the coated carbon used for carbon coating also include a doping improvement step, and the doping method includes the following steps: taking the doping raw material, distilled water and the porous carbon or coated carbon, mixing them and refluxing them for reaction, filtering after the reaction is completed, collecting the solid and drying it to obtain doped porous carbon or doped coated carbon.
[0087] In one embodiment, the doping raw material includes hydrazine hydrate.
[0088] In one embodiment, the reflux reaction time is 4-8 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, etc.
[0089] In one embodiment, in the lithium salt solution, the solvent includes at least one of water, ethanol, DMF, isopropanol, methanol, dichloromethane, cyclohexanone, etc.
[0090] In one embodiment, in the lithium salt solution, the molar concentration of the lithium salt is 0.36 mol / L.
[0091] In one embodiment, the molar ratio of lithium salt to aluminum chloride is 1:1.5.
[0092] In one embodiment, the electrolysis parameters are: electrolysis power: 15 kV; temperature: 50±5° C.;
[0093] In one embodiment, the parameters of the vapor deposition are: heating rate of the tubular furnace: 2°C / min; furnace temperature 500°C; holding time 2h; cooling rate: 2°C / min.
[0094] In one embodiment of the present application, the present application provides an application of the porous carbon composite material in preparing an electrode material.
[0095] The porous carbon composite material provided in the present application has good surface uniformity. When applied to electrode materials, it can improve the reversible capacity of the electrode material, reduce the local current density of the electrode, and inhibit the formation of lithium dendrites and the volume expansion of the electrode during the cycle.
[0096] In one embodiment of the present application, the present application provides a negative electrode plate, which includes a negative electrode collector and a negative electrode active material layer arranged on at least one side of the negative electrode collector, and the negative electrode active material layer includes the porous carbon composite material, conductive agent, thickener and binder described in the present application; based on the total mass of the negative electrode active material layer, the mass percentage of the porous carbon composite material is 95-99%.
[0097] In one embodiment, based on the total mass of the negative electrode active material layer, the mass percentage of the porous carbon composite material is 97.5-98.5%, for example, 97.5%, 97.7%, 97.9%, 98.1%, 98.3%, 98.5%, etc.
[0098] The present application has found that when the mass percentage of the porous carbon composite material in the negative electrode active material layer is further selected to be within the above range, the excellent comprehensive performance of the secondary battery can be effectively achieved.
[0099] The present application has no particular limitation on the conductive agent, thickener and binder in the negative electrode active material layer, and any conductive agent, thickener and binder conventionally selected in the art may be used.
[0100] In one embodiment of the present application, the present application provides a secondary battery, and the secondary battery includes the negative electrode plate described in the present application.
[0101] In one embodiment, the secondary battery further includes a positive electrode plate, a separator and an electrolyte.
[0102] In one embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector; the positive electrode active material layer includes a positive electrode active material. The present application has no limitation on the positive electrode active material, and any known positive electrode active material can be used.
[0103] In one embodiment, the electrolyte further comprises an organic solvent and a lithium salt. The present application has no limitation on the organic solvent and the lithium salt in the electrolyte, and any known organic solvent and lithium salt can be used.
[0104] Exemplarily, the organic solvent includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate; the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.
[0105] In one embodiment, the separator of the secondary battery is disposed between the positive electrode and the negative electrode.
[0106] Example 1
[0107] The present application provides a porous carbon composite material, a negative electrode sheet and a secondary battery. The preparation method of the porous carbon composite material, the negative electrode sheet and the secondary battery comprises the following steps:
[0108] (1) Preparation of porous carbon composites
[0109] S1. Hydrazine hydrate, distilled water and porous carbon (purchased from Shanghai Juna Technology Co., Ltd.) were added to a three-necked flask, stirred evenly and refluxed at 100°C for 6 hours. After the reflux, the mixture was filtered and washed. The solid was collected and placed in a vacuum drying oven at 25°C for 24 hours to obtain nitrogen-doped porous carbon.
[0110] S2, take hydrazine hydrate, distilled water and coated carbon (purchased from Shanghai Aladdin Reagent Co., Ltd.) into a three-necked flask, stir evenly, and reflux at 100°C for 6 hours. After the reflux, filter and wash, collect the solid, place it in a vacuum drying oven at 25°C and dry it for 24 hours to obtain nitrogen-doped coated carbon;
[0111] S3, dissolving 3.8 g of lithium perchlorate in 100 mL of distilled water to obtain a lithium salt solution, then adding nitrogen-doped porous carbon to the lithium salt solution and stirring for 30 min, and then ultrasonically treating at a frequency of 80 KHz for 30 min to obtain a suspension;
[0112] S4, adding aluminum chloride to the suspension, mixing evenly, and then adding to a high-temperature electrolytic cell for electrolysis. After the electrolysis is completed, centrifuge, collect the solid, and calcine it at 1100° C. for 2 h under nitrogen protection to obtain an intermediate;
[0113] S5, carbon-coating the intermediate with nitrogen-doped carbon by vapor deposition, and then freeze-drying under vacuum conditions for 24 hours to obtain a porous carbon composite material;
[0114] (2) Preparation of negative electrode sheet
[0115] The porous carbon composite material prepared in step (1), the conductive agent (acetylene black), the binder (styrene-butadiene rubber), and the thickener (sodium carboxymethyl cellulose) are fully stirred in deionized water at a mass ratio of 98.1:0.6:0.6:0.7, and then coated on a copper foil, and dried, rolled, and slit to obtain a negative electrode sheet;
[0116] (3) Preparation of positive electrode sheet
[0117] The positive electrode material lithium cobalt oxide, the conductive agent (acetylene black), and the binder (polyvinylidene fluoride) are fully stirred and mixed in N-methylpyrrolidone at a mass ratio of 97.6:1.5:0.9, and then coated on an aluminum foil, and then dried, rolled, and slit to obtain a positive electrode sheet;
[0118] (4) Preparation of electrolyte
[0119] A solution prepared by mixing lithium salt LiPF6 and a non-aqueous organic solvent (the mass ratio of ethylene carbonate: diethyl carbonate: propylene carbonate: propyl propionate: vinylene carbonate is 20:24:18:27:17) in a mass ratio of 7.5:92.5 is used as an electrolyte for a lithium battery;
[0120] (5) Preparation of secondary batteries
[0121] The prepared positive electrode sheet, negative electrode sheet, separator (polypropylene porous polymer film) and other battery components are assembled, and a secondary battery is obtained through processes such as shaping, baking, packaging, liquid injection, formation, and capacity division.
[0122] Example 2-3
[0123] The embodiment of the present application provides a porous carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the amounts of porous carbon, lithium metal and coated carbon in the preparation of the porous carbon composite material are adjusted to achieve the parameters in Table 1.
[0124] Embodiment 4-7
[0125] The embodiment of the present application provides a porous carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the calcination parameters during the preparation of the porous carbon composite material are adjusted to achieve the parameters in Table 1.
[0126] Embodiment 8-9
[0127] The embodiment of the present application provides a porous carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the ultrasonic power during the preparation of the porous carbon composite material is adjusted to achieve the parameters in Table 1.
[0128] Embodiment 10-11
[0129] The embodiment of the present application provides a porous carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the calcination and freeze-drying parameters in the preparation process of the porous carbon composite material are adjusted to achieve the parameters in Table 1.
[0130] Example 12
[0131] The embodiment of the present application provides a porous carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the doping process parameters of the porous carbon and the coated carbon are adjusted to achieve the parameters in Table 1.
[0132] Example 13
[0133] The present application embodiment provides a porous carbon composite material, a negative electrode plate and a secondary battery. The only difference from Embodiment 1 is that the porous carbon and the coated carbon are not doped to achieve the parameters in Table 1.
[0134] Comparative Example 1-2
[0135] The comparative example of the present application provides a porous carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the amounts of porous carbon, lithium metal and coated carbon in the preparation of the porous carbon composite material are adjusted to achieve the parameters in Table 1.
[0136] Comparative Example 3
[0137] The comparative example of the present application provides a porous carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that no carbon coating is performed to achieve the parameters in Table 1.
[0138] Comparative Examples 4-5
[0139] The comparative example of the present application provides a porous carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the parameters of ultrasound during the preparation of the porous carbon composite material are adjusted to achieve the parameters in Table 1.
[0140] The mass percentages of porous carbon, lithium metal and carbon coating in the porous carbon composite material in the embodiments and comparative examples, the specific surface area BET and pore volume V of the porous carbon composite material, the average number n of lithium metal particles in an area of 100nm×100nm of the porous carbon composite material, the thickness d1 of the core of the porous carbon composite material, the thickness d2 of the carbon coating layer of the porous carbon composite material, the doping elements and doping amounts of the porous carbon, and the doping elements and doping amounts of the coated carbon are shown in Table 1;
[0141] Table 1
[0142]
[0143] The cycle performance and energy density of the secondary batteries prepared in the examples and comparative examples are shown in Table 2; wherein the test method comprises the following steps:
[0144] 1) In an environment of 25°C, the first charge and discharge were performed, constant current and constant voltage charging was performed at a charging current of 0.5C until the upper limit voltage was 4.53V, and then constant current discharge was performed at a discharge current of 0.7C until the final voltage was 3V, and the discharge capacity ED value of the first cycle was recorded; then 400 charge and discharge cycles were performed, and the thickness at the initial and 400th cycles was recorded;
[0145] 2) Thickness change rate = (thickness after 400 cycles - initial thickness) / initial thickness × 100%;
[0146] Table 2
[0147]
[0148] It can be seen from Table 2 that when the porous carbon composite material prepared by the method provided by the present application is used as a negative electrode material in the preparation of a secondary battery, the obtained secondary battery has excellent cycle performance and high energy density; specifically, the thickness change rate of the obtained secondary battery after 400 cycles is less than 9.0%, and the ED value of the obtained secondary battery is above 703.2Wh / L;
[0149] The number of lithium metals per unit area n and the thickness of the carbon coating layer d2 are related as follows: 25≤(n*d2) / 2≤62.5; the more lithium is loaded, the more lithium may be exposed on the porous carbon surface, which requires a thicker coating layer to prevent the side reaction between lithium and the electrolyte in the system, but at the same time, the coating layer should not be too thick, which will cause the lithium ions and electrons in the product to be blocked from being deintercalated and transported, resulting in excessive local current density, affecting the safety performance of the battery cell; at the same time, the core radius d1 and the coating thickness d2 are related as follows: 15.6≤(d1+d2)*0.3≤22.5; the volume and component ratio of the composite material are limited, and a carbon skeleton that is too large will lead to a large volume of the composite material, affecting the compaction and rebound of the negative electrode material and the bonding force of the electrode, and a coating that is too thick will affect the ion transmission efficiency; similarly, a carbon skeleton that is too small will affect the deposition of lithium metal, and a carbon coating that is too thin will not be able to isolate lithium metal from the electrolyte well;
[0150] Specifically, it can be seen from Examples 1-3 and Comparative Examples 1-2 that when the mass percentages of the porous carbon, lithium metal and carbon coating in the porous carbon composite material are not within the range given in the present application, the cycle performance and energy density of the obtained secondary battery both show a significant downward trend; it can be seen from Example 1 and Comparative Example 3 that when no carbon coating is performed, the thickness change of the obtained secondary battery before and after the cycle is more obvious; it can be seen from Example 1, Examples 8-9 and Comparative Examples 4-5 that when the average number of lithium metal particles in the 100nm×100nm area of the porous carbon composite material is not within the range given in the present application, the comprehensive performance of the obtained secondary battery is also significantly reduced.
[0151] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A porous carbon composite material, characterized in that: The porous carbon composite material comprises a core and a carbon coating layer, wherein the core comprises porous carbon and lithium metal attached to the pore walls of the porous carbon; Based on the total mass of the porous carbon composite material, the mass percentage of the porous carbon is 80-88%, the mass percentage of the lithium metal is 8-16%, and the mass percentage of the carbon coating layer is 3-5%; The specific surface area of the porous carbon composite material is 500-920 m 2 / g, pore volume V is 0.4-0.9cc / g; The average number n of lithium metal particles in the porous carbon composite material with an area of 100nm×100nm is 20-30; The porous carbon composite material satisfies: 25≤A≤62.5, Where A = (n*d2) / 2; d2μm is the thickness of the carbon coating layer.
2. The porous carbon composite material according to claim 1, characterized in that The porous carbon composite material satisfies: 15.6≤D≤22.5, Where, D = (d1 + d2) * 0.3; d1μm is the radius of the inner core of the porous carbon composite material.
3. The porous carbon composite material according to claim 2, characterized in that: The radius d1 of the inner core of the porous carbon composite material is 50-70 μm, and the thickness d2 of the carbon coating layer of the porous carbon composite material is 2-5 μm.
4. The porous carbon composite material according to claim 1, characterized in that: The porous carbon is doped porous carbon, and the doping atoms of the doped porous carbon include at least one of nitrogen, boron and oxygen; And / or, based on the total mass of the porous carbon, the mass percentage of the doping atoms is 2-5%.
5. The porous carbon composite material according to claim 1, characterized in that: The carbon coating layer is a doped carbon coating layer, and the doping atoms of the doped carbon coating layer include at least one of nitrogen, boron and oxygen; And / or, based on the total mass of the carbon coating layer, the mass percentage of the doping atoms is 2-5%.
6. The method for preparing the porous carbon composite material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) mixing the lithium salt solution and the porous carbon with stirring and ultrasonication to obtain a suspension; (2) adding aluminum chloride to the suspension for electrolysis, centrifuging after electrolysis, collecting the solid and calcining to obtain an intermediate; (3) The intermediate is carbon-coated and then vacuum-freezed to obtain a porous carbon composite material.
7. The preparation method according to claim 6, characterized in that: In the step (1), the frequency of ultrasound is 60-100 KHz, and the time of ultrasound is 20-40 min; And / or, in step (2), the calcination temperature is 1000-1200° C., and the calcination time is 1.5-2.5 h; And / or, in step (3), the vacuum freeze-drying temperature is -25 to -30°C, and the vacuum freeze-drying time is 20 to 28 hours.
8. The preparation method according to claim 6, characterized in that: The lithium salt includes at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium boron trifluoride, lithium hexafluorophosphate, lithium tetrahydrofuran ester, 3,4-dihydroxybenzonitrile dilithium, n-butyl lithium, methyl lithium, and phenyl lithium.
9. Use of the porous carbon composite material according to any one of claims 1 to 5 in the preparation of electrode materials.
10. A negative electrode plate, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises the porous carbon composite material according to any one of claims 1 to 5, a conductive agent, a thickener and a binder; Based on the total mass of the negative electrode active material layer, the mass percentage of the porous carbon composite material is 95-98%.
11. A secondary battery, characterized in that: The secondary battery comprises the negative electrode sheet as claimed in claim 10.